Long-Term Follow-Up in Infantile-Onset Lambert-Eaton Myasthenic Syndrome. (September 2014) - Portaro, S.; Parisi, D.; Polizzi, A.; Ruggieri, M.; Andreetta, F.; Bernasconi, P.; Toscano, A.; Rodolico, C.
Lambert-Eaton myasthenic syndrome is a neuromuscular junction disorder characterized by proximal limb muscle weakness, fatigability, decreased deep-tendon reflexes, and autonomic symptoms. There are 2 forms of Lambert-Eaton myasthenic syndrome: one most frequently associated with small-cell lung cancer (P–Lambert-Eaton myasthenic syndrome) and the other that is a pure autoimmune form (NP–Lambert-Eaton myasthenic syndrome). Lambert-Eaton myasthenic syndrome is a very rare disorder in children younger than age 12 years. Herein, we report a 25-year-old man with NP–Lambert-Eaton myasthenic syndrome, which onset was at the age of 10 years. To date, this is the most long-term follow-up of NP–Lambert-Eaton myasthenic syndrome in childhood. In our patient, the only symptomatic treatment with 3, 4-diaminopyridine phosphate has been sufficient to guarantee him a good quality of life. Our data remind physicians to keep in mind the diagnosis of Lambert-Eaton myasthenic syndrome in children with a proximal myopathic pattern and they confirm the specificity of compound muscle action potential incremental pattern after brief maximal effort in Lambert-Eaton myasthenic syndrome.